Canine angiostrongylosis: recent advances in diagnosis, prevention, and treatment - Di Cesare, Angela (Vet Med (Auckl), 2014)
Angiostrongylus vasorum is a parasitic nematode affecting the heart and pulmonary arteries of wild (eg, foxes) and domestic canids. The parasite has an indirect life cycle in which slugs and snails act as intermediate hosts. In the last few years the parasite has spread outside the traditional endemic foci, and there is a rise of documented cases of canine angiostrongylosis across Europe. Angiostrongylus vasorum causes cardiopulmonary disorders and coagulopathies, along with different nonspecific clinical signs. Fatal infections are frequently reported. Given the severity of the infection and the recent geographic spreading of the parasite, this article reviews and discusses the current knowledge of A. vasorum, with a special focus on recent insights on diagnosis, prevention, and treatment of dog angiostrongylosis.